Preventive and Responsive Intervention Strategies of Teachers in School Bullying - Doyoung Seong (Research and Advances in Education, 2024)
School bullying is a persistent issue that negatively impacts students’ psychological well-being, academic performance, and social development. In South Korea, where societal hierarchies and academic pressures are prevalent, addressing bullying requires a comprehensive approach involving both preventive and responsive strategies. This paper examines the pivotal role of teachers in combating school bullying, focusing on their preventive and intervention tactics. Preventive strategies emphasize fostering a positive school climate, enhancing teacher-student relationships, and promoting empathy among students. Responsive strategies, meanwhile, involve immediate and effective intervention through restorative practices, behavioral counseling, and emotional support for victims. Additionally, the paper highlights the critical influence of school climate and leadership in shaping the efficacy of anti-bullying measures. Strong leadership provides the necessary framework for consistent policy enforcement and resource allocation, empowering teachers to act confidently. This study underscores the importance of integrating prevention, intervention, and leadership to create a safer and more supportive educational environment. By analyzing current practices and offering evidence-based recommendations, this research aims to guide schools in reducing bullying and fostering a nurturing atmosphere conducive to learning and personal growth.